ANALYSIS OF THE IMPLEMENTATION OF HUMAN RESOURCES DEVELOPMENT AND TRAINING POLICIES IN AISYIYAH II KARTASURA KINDERGARTEN - RAHMANTO, RAHMANTO; NOVITASARI, AYU; MAFILINDA, RISA AHWALINA; AZ-ZAHRA, BERLIAN; SUPRAPRTI, SUPRAPRTI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
This study aims to analyze the implementation of human resource development and training policies at Aisyiyah II Kartasura Kindergarten. The focus of this research is to understand how the human resource development policies are implemented, the challenges faced, and their impact on the quality of teachers and supporting staff. The research approach used is qualitative with a descriptive method, where data is collected through in-depth interviews, observation, and documentation. The results show that the human resource development and training policies at Aisyiyah II Kartasura Kindergarten have been implemented as planned, although some challenges remain, such as budget constraints and training time limitations. The training programs provided include improving pedagogical competence, technological skills, and strengthening religious values. These policies have positively impacted the improvement of teaching quality and the ability of teachers to face modern educational challenges. In conclusion, the implementation of human resource development and training policies at Aisyiyah II Kartasura Kindergarten plays a significant role in improving the quality of education, although improvements are still needed in terms of funding and scheduling. The recommendations provided include increasing budget allocation for training and creating a more flexible training schedule to ensure optimal program execution. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi kebijakan pengembangan dan pelatihan sumber daya manusia di TK Aisyiyah II Kartasura. Fokus penelitian ini adalah untuk memahami bagaimana kebijakan pengembangan sumber daya manusia dilaksanakan, tantangan yang dihadapi, dan dampaknya terhadap kualitas guru dan tenaga pendukung. Pendekatan penelitian yang digunakan adalah kualitatif dengan metode deskriptif, dimana data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa kebijakan pengembangan sumber daya manusia dan pelatihan di TK Aisyiyah II Kartasura telah dilaksanakan sesuai rencana, meskipun masih terdapat beberapa kendala seperti kendala anggaran dan keterbatasan waktu pelatihan. Program pelatihan yang diberikan meliputi peningkatan kompetensi pedagogik, keterampilan teknologi, dan penguatan nilai-nilai keagamaan. Kebijakan-kebijakan ini berdampak positif pada peningkatan kualitas pengajaran dan kemampuan guru dalam menghadapi tantangan pendidikan modern. Kesimpulannya, implementasi kebijakan pengembangan sumber daya manusia dan pelatihan di TK Aisyiyah II Kartasura sangat berperan dalam peningkatan mutu pendidikan, meskipun masih diperlukan perbaikan dari segi pendanaan dan penjadwalan. Rekomendasi yang diberikan antara lain meningkatkan alokasi anggaran untuk pelatihan dan membuat jadwal pelatihan yang lebih fleksibel untuk memastikan pelaksanaan program yang optimal.